Nanobiotecnologia aplicada à transgênese animal. - Campos, Vinicius Farias (2011)
Nanobiotechnology has provided new scientific and technological knowledge in distinct areas making it a priority area of research in developed and developing countries. The sperm-mediated gene transfer (SMGT) technique may become more simple, efficient and cost-effective technique for the generation of transgenic animals. The development of nanocomposites able to carry foreign DNA into the nucleus of cells with greater efficiency allows techniques such as SMGT be improved. The NanoSMGT is a technique used to generate transgenic animals in which nanotechnology is used to enhance the ability of sperm to capture exogenous DNA. The objective of this study was to determine whether cationic nanopolymer or halloysite clay nanotubes are able to transfect the exogenous DNA to unsorted and sex-sorted bovine sperm then evaluate whether these sperm are able to transmit transgene to in vitro fertilized bovine embryos. Using real-time PCR, we found that the cationic nanopolymer is capable of introducing exogenous DNA into unsorted and sex-sorted bovine sperm without negative effects to sperm motility and viability. Was also demonstrated for the first time that cationic nanopolymer or halloysite clay nanotubes are able to increase both the sperm DNA transfection of as the transmission of the transgene to bovine embryos produced in vitro. These results demonstrate that NanoSMGT can be a viable technique for producing transgenic bovine embryos.